New approaches to rural policy lessons from around the world. (OECD, 2005)
This book presents the proceedings of a conference held near Washington, DC (Airlie, Virginia) to discuss the need for innovative new approaches to rural policy. U.S. Federal Reserve Chairman Alan Greenspan opened the conference by stressing the crucial importance of flexibility in enhancing economic welfare and economic growth, cautioning policy makers to be careful when utilizing subsidies as they have exceptionally negative long-term implications. Other presentations discuss regional partnerships, redefining regions, rural entrepreneurship, rural policy and regional development, federal coordination, and the future of rural policy.--Publisher's description.